2020
DOI: 10.1371/journal.pone.0233464
|View full text |Cite
|
Sign up to set email alerts
|

Variants in IL23R-C1orf141 and ADO-ZNF365-EGR2 are associated with susceptibility to Vogt-Koyanagi-Harada disease in Japanese population

Abstract: Vogt-Koyanagi-Harada (VKH) disease is a systemic inflammatory disorder that affects pigment cell-containing organs such as the eye (e.g., chronic and/or recurrent granulomatous panuveitis). While the exact etiology and pathogenic mechanism of VKH disease are unclear, HLA-DR4 alleles have been documented to be strongly associated with VKH disease in various ethnic groups. Recently, a genome-wide association study (GWAS) found two new genetic risk factors (IL23R-C1orf141 and ADO-ZNF365-EGR2) in a non-HLA region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…This study identified two new susceptibility loci associated with VKH disease reached genome-wide significance, IL23R-C1orf141 (rs117633859) and ADO-ZNF365-EGR2 (rs442309), it being of particular interest that these associations are shared by uveitis associated with both BD and AAU. These findings have recently been replicated in a Japanese case-control candidate gene association study [ 49 ]. Hou et al also demonstrated association between HLA genes and VKH disease, showing the strongest association with SNP at HLA-DRB1/DQA1 locus (rs3021304).…”
Section: Vogt-koyanagi-harada Diseasementioning
confidence: 72%
“…This study identified two new susceptibility loci associated with VKH disease reached genome-wide significance, IL23R-C1orf141 (rs117633859) and ADO-ZNF365-EGR2 (rs442309), it being of particular interest that these associations are shared by uveitis associated with both BD and AAU. These findings have recently been replicated in a Japanese case-control candidate gene association study [ 49 ]. Hou et al also demonstrated association between HLA genes and VKH disease, showing the strongest association with SNP at HLA-DRB1/DQA1 locus (rs3021304).…”
Section: Vogt-koyanagi-harada Diseasementioning
confidence: 72%
“…The C1orf141 gene, with uncharacterized protein function, has overlapping regions with IL23R . Variants in the IL23R-C1orf141 region have been associated with susceptibility to Vogt-Koyanagi-Harada disease, a multi-system autoimmune disorder that affects pigmented tissues, in Chinese and Japanese populations [ 31 , 54 ]. The ZFR gene encodes the highly conserved zinc finger RNA-binding protein, which is shown to prevent excessive type I interferon activation by regulating alternative pre-mRNA splicing [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Disease susceptibility has been reported for MHC class II genes, such as HLA-DR4/DRw53, and HLA-DQ4 In VKH disease (68) A GWAS of a Chinese cohort including 1,538 cases and 5,603 controls reported disease susceptibility loci of IL23R and ADO-EGR2 (41). Disease susceptibility of IL23R was confirmed in the Han Chinese Singaporean and Japanese populations, and ADO-EGR2 was confirmed in the Japanese and Thai populations (42,43).…”
Section: Vogt-koyanagi-harada Diseasementioning
confidence: 96%